Nox2+ myeloid cells drive vascular inflammation and endothelial dysfunction in heart failure after myocardial infarction via angiotensin II receptor type 1. Issue 1 (20th February 2020) - Molitor, Michael; Rudi, Wolf-Stephan; Garlapati, Venkata; Finger, Stefanie; Schüler, Rebecca; Kossmann, Sabine; Lagrange, Jeremy; Nguyen, Thanh Son; Wild, Johannes; Knopp, Tanja; Karbach, Susanne H; Knorr, Maike; et al.
Abstract: Aims: Heart failure (HF) ensuing myocardial infarction (MI) is characterized by the initiation of a systemic inflammatory response. We aimed to elucidate the impact of myelomonocytic cells and their activation by angiotensin II on vascular endothelial function in a mouse model of HF after MI. Methods and results: HF was induced in male C57BL/6J mice by permanent ligation of the left anterior descending coronary artery. Compared to sham, HF mice had significantly impaired endothelial function accompanied by enhanced mobilization of Sca-1 + c-Kit + haematopoietic stem cells and Sca-1 − c-Kit + common myeloid and granulocyte-macrophage progenitors in the bone marrow as well as increased vascular infiltration of CD11b + Ly6G − Ly6C high monocytes and accumulation of CD11b + F4/80 + macrophages, assessed by flow cytometry. Using mice with Cre-inducible expression of diphtheria toxin receptor in myeloid cells, we selectively depleted lysozyme M + myelomonocytic cells for 10 days starting 28 days after MI. While the cardiac phenotype remained unaltered until 38 days post-MI, myeloid cell depletion attenuated vascular accumulation of Nox2 + CD45 + cells, endothelial dysfunction, oxidative stress, and vascular expression of adhesion molecules and angiotensin II receptor type 1 (AT1R). Pharmacological blockade of this receptor for 4 weeks did not significantly alter cardiac function, but mimicked the effects of myeloid cell depletion: telmisartan (20 mg/kg/day, fed to C57BL/6J mice) diminished bone marrow myelopoesis and myeloid reactive oxygen species production, attenuated endothelial leucocyte rolling and vascular accumulation of CD11b + Ly6G − Ly6C high monocytes and macrophages, resulting in improved vascular function with less abundance of Nox2 + CD45 + cells. Conclusion: Endothelial dysfunction in HF ensuing MI is mediated by inflammatory Nox2 + myeloid cells infiltrating the vessel wall that can be targeted by AT1R blockade. Graphical Abstract: